A ten-year review of healthcare-associated bloodstream infections from forty hospitals in Québec, Canada. (29th August 2018) - Fakih, Iman; Fortin, Élise; Smith, Marc-André; Carignan, Alex; Tremblay, Claude; Villeneuve, Jasmin; Moisan, Danielle; Frenette, Charles; Quach, Caroline
Abstract: Objective: Healthcare-associated bloodstream infections (HABSI) are a significant cause of morbidity and mortality worldwide. In Québec, Canada, HABSI arising from acute-care hospitals have been monitored since April 2007 through the Surveillance des bactériémies nosocomiales panhospitalières (BACTOT) program, but this is the first detailed description of HABSI epidemiology. Methods: This retrospective, descriptive study was conducted using BACTOT surveillance data from hospitals that participated continuously between April 1, 2007, and March 31, 2017. HABSI cases and rates were stratified by hospital type and/or infection source. Temporal trends of rates were analyzed by fitting generalized estimating equation Poisson models, and they were stratified by infection source. Results: For 40 hospitals, 13, 024 HABSI cases and 23, 313, 959 patient days were recorded, for an overall rate of 5.59 per 10, 000 patient days (95% CI, 5.54–5.63). The most common infection sources were catheter-associated BSIs (23.0%), BSIs secondary to a urinary focus (21.5%), and non–catheter-associated primary BSIs (18.1%). Teaching hospitals and nonteaching hospitals with ICUs often had rates higher than nonteaching hospitals without ICUs. Annual HABSI rates did not exhibit statistically significant changes from year to year. Non–catheter-associated primary BSIs were the only HABSI type that exhibited a sustained change across the 10 years, increasing from 0.69 per 10, 000 patient days (95% CI, 0.59–0.80) in 2007–2008 to 1.42 per 10, 000 patient days (95% CI, 1.27–1.58) in 2016–2017. Conclusions: Despite ongoing surveillance, overall HABSI rates have not decreased. The effect of BACTOT participation should be more closely investigated, and targeted interventions along alternative surveillance modalities should be considered, prioritizing high-burden and potentially preventable BSI types.